Sustainable and active ageing: Development and application of saving methodology - Almeida-Silva, M.; Manteigas,V.; Tavares, D.; Teixeira, A. M.; Carvalho, A.; Moreira, J.; Tomás, T.; Monteiro, A.; Viegas, C. ("New" challenges for the future - Abstract proceedings of International Congress on Environmental Health 2019, 2019)
SAVING project intends to develop research activities applying the best strategies and good practices regarding to the promotion of an active, healthy and sustainable ageing in relation to social, economic, environmental and pedagogic aspects. This project aims to create a Sustainable and Active Ageing Program named SAVING Program to promote the transition to a sustainable ageing in Elderly Care Centres (ECCs). SAVING Program is an ideal way for ECCs to embark on a meaningful path towards an effective and positive impact on the lives of old people, their families, ECCs staff and local authorities. Moreover, it is a massive opportunity not only to improve the ECCs environmental and physical conditions, but also to potentiate synergies with health, social and academic professionals/institutions that might open an easy and free channel between old people and societal opportunities. The project’ methodology is based on three pillars: 1) the creation of SAVING Brigade; 2) the development of a database with the definition of several indicators regarding three strands (environmental, organization and physical activity); 3) the action plan. All this innovative methodology was built on a living-lab approach applied in one ECC, that was used as casestudy.